Impact of personal, psychological, and social factors on English language learning: A non-native student case study - Muslim, Saifullah (Goodwood Publishing, 2023)
Purpose: This case study aimed to explore the impact of personal, psychological, and social factors on a non-native English language student and to determine whether the students’ errors in speaking and writing were developmental or transferred. Methodology/approach: The case study was conducted on a single participant (an English language student) at Paktia University, Afghanistan. The data were collected using four different types of instruments. The data were analyzed considering the influence of personal, psychological, and social factors on the participants’ language learning. Results/Findings: The participant faced a great number of problems caused by personal, psychological, and social factors, including lack of social motivation, lack of social practice, economic limitations, and grammatical errors in productive skills usually transferred from the native language or caused by lack of practice. However, as an extraverted and motivated learner, he overcame most of the problems during learning. He improved his speaking skills and pronunciation through self-interactions and online communication. Limitations: This was a single-participant case study; therefore, further studies are needed to generalize the findings to Afghan English language students. Contribution: This study can help policymakers, curriculum designers, educational institution authorities, and English language educators to better identify the factors that affect English language learning. Novelty: This is the only study conducted to examine the process of an individual’s English language learning process in Afghanistan.